(untitled) (Heritage, 2025)
The transformative ethos of the Transhumanist Manifesto has long ignited academic discussions around the potentialities of humankind’s evolution, primarily steered by burgeoning technologies. Within its avant-garde guidelines lies a prophetic vision: a world where human capabilities—intellectual, physical, and psychological—are significantly heightened, transcending the conventional boundaries of biology. This paper aims to revisit and critically appraise the Manifesto in light of recent advancements in the digital era, drawing connections between the imagined futures of yesteryears and our present trajectory. Centered around seminal theories, including Harari’s insights on the Homo Deus, Kurzweil’s anticipation of a technological singularity, and Bostrom’s simulation hypothesis, this investigation probes into the nuances of identity, consciousness, and sociocultural shifts in an impending age defined by its digital dominance.